Intralesional steroids and endoscopic dilation for anastomotic strictures after esophagectomy: systematic review and meta-analysis - Dasari, Chandra S.; Jegadeesan, Ramprasad; Patel, Harsh K.; Desai, Madhav; Aziz, Muhammad; Thoguluvachandrasekar, Viveksandeep; Duvvuri, Abhiram; Kohli, Divyanshoo R.; Repici, Alessandro; Siersema, Peter D.; Sharma, Prateek (Endoscopy, 2020)
Background Post-esophagectomy anastomotic strictures are difficult to treat. The impact of adding local steroid injection to endoscopic dilation for the treatment of post-esophagectomy anastomotic strictures is unclear. We conducted a systematic review and meta-analysis to assess the efficacy of performing steroid injection in addition to dilation.Methods A search was conducted in MEDLINE, Cochrane Library, EMBASE, and Web of Science from inception to January 2019. Randomized controlled trials (RCTs) comparing the efficacy of endoscopic dilation plus either local steroid injection (steroid group) or saline injection (placebo group) were included in the analysis.Results Three RCTs were eligible for the final analysis: 72 patients (mean age 61.3 years, 74 % male) in the steroid group and 72 patients (mean age 59.6 years, 71 % male) in the placebo group. The mean number of dilations required to resolve the stricture was significantly lower in the steroid group compared with the placebo group, with a mean weighted difference of –1.62 (95 % confidence interval [CI] –2.73 to –0.50; P = 0.004). After 6 months of follow-up, there was a trend toward more patients in the steroid group remaining dysphagia free compared with the placebo group, with a pooled odds ratio of 2.36 (95 %CI 0.94 to 5.91; P = 0.07, I2 = 24 %).Conclusion This meta-analysis showed that the addition of local steroid injection at the time of dilation for benign anastomotic strictures led to a significant decrease in the number of procedures required to resolve the stricture and may well reduce dysphagia symptoms during follow-up.